Glottal opening and closing events investigated by electroglottography and super-high-speed video recordings - Herbst, Christian T; Lohscheller, Jörg; Švec, Jan G; Henrich, Nathalie; Weissengruber, Gerald; Fitch, W Tecumseh (The Journal of experimental biology, 2014)
Previous research has suggested that the peaks in the first derivative (dEGG) of the electroglottographic (EGG) signal are good approximate indicators of the events of glottal opening and closing. These findings were based on high-speed video (HSV) recordings with frame rates 10 times lower than the sampling frequencies of the corresponding EGG data. The present study attempts to corroborate these previous findings, utilizing super-HSV recordings. The HSV and EGG recordings (sampled at 27 and 44 kHz, respectively) of an excised canine larynx phonation were synchronized by an external TTL signal to within 0.037 ms. Data were analyzed by means of glottovibrograms, digital kymograms, the glottal area waveform and the vocal fold contact length (VFCL), a new parameter representing the time-varying degree of 'zippering' closure along the anterior-posterior (A-P) glottal axis. The temporal offsets between glottal events (depicted in the HSV recordings) and dEGG peaks in the opening and closing phase of glottal vibration ranged from 0.02 to 0.61 ms, amounting to 0.24-10.88% of the respective glottal cycle durations. All dEGG double peaks coincided with vibratory A-P phase differences. In two out of the three analyzed video sequences, peaks in the first derivative of the VFCL coincided with dEGG peaks, again co-occurring with A-P phase differences. The findings suggest that dEGG peaks do not always coincide with the events of glottal closure and initial opening. Vocal fold contacting and de-contacting do not occur at infinitesimally small instants of time, but extend over a certain interval, particularly under the influence of A-P phase differences.
Keywords: dEGG double peaks; audiovizuální záznam; Vibration; psi; hlasové řasy; zvuková spektrografie; Dogs; Glottal opening and closing events; Sound Spectrography; Excised canine larynx; High-speed video; Glottis; ženské pohlaví; zvířata; vibrace; glottis; Video Recording; Phonation; fonace; Vocal fold contact length; Electroglottography; Vocal Cords; Female; Animals